Dark septate endophytes promote the growth of Cynodon dactylon under drought stress and enhance its potential for use in the ecological restoration of slopes - Jia, Haoji; Geng, Qiming; Li, Mingyi; Wang, Ran; Wang, Fuhao; Deng, Yuxin; Xu, Wennian; Liu, Daxiang (Frontiers in Plant Science, 2025)
IntroductionThe objective of this study was to investigate whether dark septate endophytes (DSEs) can increase plant drought tolerance in the context of vegetation concrete, which is a complex environment.MethodsThis study employed a controlled simulation experiment to investigate the influence of inoculation with diverse DSEs, namely, Paraphoma chrysanthemicola (PC), Alternaria alternata (AA), and Cladosporium cladosporioides (CC), on the growth, photosynthetic characteristics, osmoregulatory substance content, and antioxidant enzyme activities of Cynodon dactylon in vegetation concrete subjected to drought stress.ResultsThese findings demonstrated that DSEs were capable of effectively mitigating the adverse impacts of drought on plant growth. Under moderate drought (MD 55%±5% of the maximum moisture capacity in the field), DSEs increased the dry weight (DB), net photosynthetic rate (Pn), soluble sugar (SS) and peroxidase (POD) of C. dactylon by up to 14.21%, 32.63%, 40.73% and 31.43%, respectively, and reduced the malondialdehyde (MDA) content by 8.02-13.77%. Furthermore, under severe drought (SD, 35%±5% of the maximum moisture capacity in the field), DSE inoculation enhanced the photosynthetic capacity of C. dactylon, stimulated the accumulation of osmoregulatory compounds such as proline (Pro) and soluble protein (SP), and mitigated the water loss associated with drought.ConclusionThe results demonstrate that DSE inoculation enhances the drought resistance of plants used in vegetation concrete by increasing the photosynthetic rate, and contents of antioxidant enzymes and osmoregulatory substances. This study provides reference for the use of DSEs in ecological restoration with vegetation concrete.